Impact of perioperative factors on nadir serum prostate‐specific antigen levels after holmium laser enucleation of prostate. Issue 3 (5th January 2021) - Martos, Mary; Katz, Jonathan E.; Parmar, Madhumita; Jain, Anika; Soodana‐Prakash, Nachiketh; Punnen, Sanoj; Gonzalgo, Mark L.; Miao, Feng; Reis, Isildinha M.; Smith, Nicholas; Shah, Hemendra N.
Abstract: Objective: To investigate the relationship of preoperative prostate size, urinary retention, positive urine culture, and histopathological evidence of prostatitis or incidental prostate cancer on baseline and 3‐month nadir prostate‐specific antigen (PSA) value after Holmium laser enucleation of prostate (HoLEP). Patients and methods: Data from 90 patients who underwent a HoLEP by En‐bloc technique were analyzed. PSA values at baseline and at 3‐month follow‐up, preoperative urinary retention and urine culture status, weight of resected tissue, and histopathological evidence of prostatitis or prostate cancer were recorded. We performed univariable and multivariable gamma‐regression analyses to determine the impact of the aforementioned perioperative variables on preoperative PSA, 3‐month postoperative PSA, and change in PSA. Results: Serum PSA reduced significantly at 3 months from 6.3 ± 5.9 ng/mL to 0.6 ± 0.6 ng/mL. On both univariable and multivariable analysis, 3‐month nadir level was independent of all preoperative factors examined, except preoperative urinary retention status. Although patients with smaller prostate (resected tissue weight <40 g) had less percentile reduction in PSA when compared with those with larger prostate (resected tissue weight >80 g) (77.67% vs 89.06%; P < .001), patients from both these groups noted a similar PSA nadir level after 3 months (0.54 vs 0.56 ng/dL). The drop in PSA level after HoLEP remained stable up to 1‐year follow‐up. Conclusions: PSA nadir 3 months after HoLEP remains relatively consistent across patients, regardless of preoperative prostate size, PSA value, urine culture status, and histopathological evidence of prostatitis or incidental prostate cancer.